Judicial Decision-Making in Personal Injury Cases: A Comprehensive Analysis of Factors, Constraints, and Theoretical Frameworks - Barnawi, Fatimah Abdulrahman (Journal of Economic, Administrative and Legal Sciences, 2025)
The analysis explores the constraints faced by judges and elucidates how these challenges shape their decision-making. Additionally, the paper critically evaluates the leading theories proposed by scholars to understand judicial behavior, ultimately arguing that strategic theory offers the most holistic and nuanced understanding. Unlike models that treat judges as either mechanical interpreters of the law or purely ideological actors, the strategic approach accounts for the broader institutional and interpersonal dynamics that influence judicial conduct. This research aims to contribute to the scholarly understanding of judicial decision-making, particularly in the context of personal injury cases. The findings demonstrate the multifaceted nature of the factors that judges must consider, highlighting the need for a comprehensive approach to analyzing their behavior.